Oncological outcomes of laparoscopic radical hysterectomy versus radical abdominal hysterectomy in patients with early-stage cervical cancer: A multicenter analysis - Rodriguez, Juliana (2021)
Introduction Recent evidence has shown adverse oncological outcomes when minimally invasive surgery is used in early-stage cervical cancer. The objective of this study was to compare disease-free survival in patients that had undergone radical hysterectomy and pelvic lymphadenectomy, either by laparoscopy or laparotomy. Methods We performed a multicenter, retrospective cohort study of patients with cervical cancer stage IA1 with lymph-vascular invasion, IA2, and IB1 (FIGO 2009 classification), between January 1, 2006 to December 31, 2017, at seven cancer centers from six countries. We included squamous, adenocarcinoma, and adenosquamous histologies. We used an inverse probability of treatment weighting based on propensity score to construct a weighted cohort of women, including predictor variables selected a priori with the possibility of confounding the relationship between the surgical approach and survival. We estimated the HR for all-cause mortality after radical hysterectomy with weighted Cox proportional hazard models. Results A total of 1379 patients were included in the final analysis, with 681 (49.4%) operated by laparoscopy and 698 (50.6%) by laparotomy. There were no differences regarding the surgical approach in the rates of positive vaginal margins, deep stromal invasion, and lymphovascular space invasion. Median follow-up was 52.1 months (range, 0.8-201.2) in the laparoscopic group and 52.6 months (range, 0.4-166.6) in the laparotomy group. Women who underwent laparoscopic radical hysterectomy had a lower rate of disease-free survival compared with the laparotomy group (4-year rate, 88.7% vs 93.0%; HR for recurrence or death from cervical cancer 1.64; 95% CI 1.09-2.46; P=0.02). In sensitivity analyzes, after adjustment for adjuvant treatment, radical hysterectomy by laparoscopy compared with laparotomy was associated with increased hazards of recurrence or death from cervical cancer (HR 1.7; 95% CI 1.13 to 2.57; P=0.01) and death for any cause (HR 2.14; 95% CI 1.05-4.37; P=0.03). Conclusion In this retrospective multicenter study, laparoscopy was associated with worse disease-free survival, compared to laparotomy.